Epoxidation of allyl alcohol to glycidol over TPAOH-treated titanium silicalite-1 extrudates - Ocran, Gideon Abaidoo; Zhang, Bosong; Zuo, Yi; Tan, Huali; Li, Gudan; Yang, Hong; Song, Chunshan; Guo, Xinwen (Frontiers in Chemical Engineering, 2026)
The epoxidation of allyl alcohol with H2O2 over titanium silicalite-1 (TS-1) is an environmentally friendly route for producing glycidol. However, the catalytic activity and stability of TS-1 is not satisfactory. In this study, strip-shaped TS-1 was hydrothermally treated by TPAOH solution, change theTi coordination states and diffusion property, thereby enhancing its catalytic performance. The influences of TPAOH concentration and treating time on the physical chemical property and catalytic performance were studied systematically. It was found that the SiO2 agglomerant was dissolved and crystallized during the treatment, resulting in an increased Si content on the external surface. The tetrahedrally coordinated Ti was transformed to pentahedrally and octahedrally coordinated Ti, which possess higher catalytic activity for selective oxidation. The treatment also leads to the formation of cavities in the TS-1 crystals, which can shorten the diffusion pathway of substates and improve the diffusion property. Both the chemical property and microstructure enhance the catalytic activity for allyl alcohol epoxidation.